1984
DOI: 10.1002/j.1551-8833.1984.tb05302.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effects on the Use of Metal‐Ion Coagulants for Water Treatment

Abstract: The effects of low‐temperature conditions on the use of alum and ferric chloride for the removal of turbidity were studied. Experimental work involved the use of these coagulants for the removal of kaolin from water samples under both extreme‐low‐temperature and room‐temperature conditions. Analysis of data from a full‐scale treatment plant that experienced failure at low temperature was also included. Temperature effects on coagulation were significant, with low‐temperature conditions producing sharp decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
2

Year Published

1986
1986
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 3 publications
(2 reference statements)
4
50
0
2
Order By: Relevance
“…The floc size was small when it was observed with the naked eye at 5 o C, and the formation of floc was difficult to identify during the process of slow agitation. This was consistent with the report of Morris and Knocke [1984] that showed a decrease in the turbidity removal and smaller flocs under low temperature with alum as a coagulant. It was observed that ferric chloride was less sensitive in the changes in temperature than was PAC.…”
Section: Effect Of Ph and Temperature On Removal Of Doc And Turbiditysupporting
confidence: 94%
See 2 more Smart Citations
“…The floc size was small when it was observed with the naked eye at 5 o C, and the formation of floc was difficult to identify during the process of slow agitation. This was consistent with the report of Morris and Knocke [1984] that showed a decrease in the turbidity removal and smaller flocs under low temperature with alum as a coagulant. It was observed that ferric chloride was less sensitive in the changes in temperature than was PAC.…”
Section: Effect Of Ph and Temperature On Removal Of Doc And Turbiditysupporting
confidence: 94%
“…Morris and Knocke reported that ferric chloride was less influenced at a low temperature compared with alum, and they suggest the combination of alum and ferric chloride as a potential method [14]. However, Johnson and Amirtharajah reported the coagulation performance was not evidently enhanced by the combination of alum and ferric chloride [27].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The optimum pH varies inversely with temperature. Morris and Knocke (1984) reported that with either alum coagulation or ferric chloride coagulation, the floes at 1 °C are generally smaller than those formed at 20°C (Figure 6-3 (a) and (b)). They also found that low temperature has a significant effect on turbidity removal for both coagulants, as shown in Figure 6-3 (c) and (d), although the effect was not as severe for ferric chloride as for aluminum sulfate.…”
Section: Coagulation and Flocculationmentioning
confidence: 92%
“…Pour MOHTADI et RAO (1973) et KOWAL et MACKIEWICZ (1975, cette dégradation est due au pH optimum de coagulation qui croît lorsque la température s'abaisse, DOLEJS (1983,1984), dans deux études consécutives sur des eaux chargées en matières humiques, montre lui, qu'une agitation plus intense après l'injection du coagulant peut, à faible température, améliorer le rendement d'élimination des colloïdes et que selon l'alcalinité du milieu l'effet de la température peut varier. L'action limitante de la température peut également être atténuée, comme le précisent MORRIS et KNOCKE (1984), en augmentant la concentration des matières en suspension. En 1986, BAZER-BACHI confirme le déplacement du pH optimum de coagulation avec la température sur des eaux qui ont des caractéristiques physico-chimiques proches de celles de la Garonne.…”
Section: Pour Pallier Ces Inconvénients Le Service Des Eaux De La VIunclassified